Original articleCXCL1 (GRO-alpha) chemokine in acute ischaemic stroke patients - Losy, Jacek; Zaremba, Jarosław; Skrobański, Piotr (Folia Neuropathologica, 2005)
The inflammation accompanies and exacerbates cerebral ischaemia. The infiltrated leucocytes are thought to contribute to tissue injury in stroke patients. GRO-alpha (CXCL1) is a potent neutrophil chemoattractant which may play an important role in pathophysiology of stroke. 23 ischaemic stroke patients and 15 controls have been studied. CSF and blood sampling together with cranial CT were performed within first 24 hours of stroke. CXCL1 levels were determined by ELISA, and volume of stroke-related brain CT hypodense areas was calculated. Stroke patients displayed significantly higher CSF CXCL1 level than controls (65.6±22.3 vs 43.8±2.3 pg/ml; p<0.01). Serum CXCL1 levels in stroke patients did not differ from controls. CSF CXCL1 level correlated positively with volume of brain CT hypodense areas (p<0.001). The results suggest that CXCL1 may be involved in inflammatory reaction during an early phase of ischaemic stroke.